"Influencia de la temperatura y la agitación del medio corrosivo constituido por acido sulfamico (h2nso3h-0.5m), sobre la velocidad de corrosión de los aceros astm a335 grado p22, astm a335 grado p91, y astm a213 grado t92, medido mediante diferentes técnicas electroquímicas” - Cholan Quispe, Miguel Angel (2015)
The corrosion behaviour of ASTM A335 P22, ASTM A335 P91 and ASTM A213 T92 steels, in a solution of H2NSO4H-0.5M at different temperatures (298-338 K) and stirring velocities (0 – 700 rpm) was investigated, using methods: Tafel extrapolation, linear polarization resistance, electrochemical impedance spectroscopy and electrochemical frequency modulation The corrosion rate of steel so increased exponentially with temperature. This effect is more pronounced in P22 steel, being the order of corrosion resistance at 338 K (65oC), T92  P91  P22. Likewise, increased stirring results in increased corrosion rate, with greater effect in the P22 steel. Increasing both the temperature and stirring of the acid solution produced on the surface of the steels a depolarization hydrogen evolution reaction. The corrosion rate data obtained with the four techniques evaluated show good agreement. Keywords: